Characterization and Expression Analysis of Toll-Like Receptor 3 Cdna from Atlantic Salmon (Salmo Salar) - Vidal-Soto, R (Fundacao de Pesquisas Cientificas de Ribeirao Preto, 2015)
Innate pathway activation is fundamental for early anti-viral defense in fish, but currently there is insufficient understanding of how salmonid fish identify viral molecules and activate these pathways. The Toll-like receptor (TLR) is believed to play a crucial role in host defense of pathogenic microbes in the innate immune system. In the present study, the full-length cDNA of Salmo salar TLR3 (ssTLR3) was cloned. The ssTLR3 cDNA sequence was 6071 bp long, containing an open reading frame of 2754 bp and encoding 971 amino acids. The TLR group motifs, such as leucine-rich repeat (LRR) domains and Toll-interleukin-1 receptor (TIR) domains, were maintained in ssTLR3, with sixteen LRR domains and one TIR domain. In contrast to descriptions of the TLR3 in rainbow trout and the murine (TATA-less), we found a putative TATA box in the proximal promoter region 29 bp upstream of the transcription start point of ssTLR3. Multiple-sequence alignment analysis of the ssTLR3 protein-coding sequence with other known TLR3 sequences showed the sequence to be conserved among all species analyzed, implying that the function of the TLR3 had been sustained throughout evolution. The ssTLR3 mRNA expression patterns were measured using real-time PCR. The results revealed that TLR3 is widely expressed in various healthy tissues. Individuals challenged with infectious pancreatic necrosis virus and immunostimulated with polyinosinic:polycytidylic acid exhibited increased expression of TLR3 at the mRNA level, indicating that ssTLR3 may be involved in pathogen recognition in the early innate immune system. © FUNPEC-RP.